2011
DOI: 10.1590/s0102-695x2011005000052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of post-surgical healing in rats using a topical preparation based on extract of Musa sapientum L., Musaceae, epicarp

Abstract: Abstract:Considering that oral preparations made with peel green bananas (e.g. flour and extracts) demonstrated healing effects on mucous membranes and skin, this study evaluated the healing and the antimicrobial property of a topical preparation based on extract of Musa sapientum L., Musaceae, (apple banana) in surgically induced wounds in the skin of male Wistar rats, 100 g. The extract was obtained by decoction, the presence of tannins was detected by phytochemical screening and 10% of the extract was incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Although FTIR analysis was not conclusive, it showed strong evidences of the presence of tannins in unripe banana peel and membranes. Tannins show antimicrobial activity, which plays an important role in wound healing applications [9][10][11][12][13]. We recently demonstrated the efficiency of chitosan membranes associated with unripe banana peel extracts on the growth inhibition of Staphylococcus aureus and Escherichia coli, most common bacteria found in skin wounds [9].…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although FTIR analysis was not conclusive, it showed strong evidences of the presence of tannins in unripe banana peel and membranes. Tannins show antimicrobial activity, which plays an important role in wound healing applications [9][10][11][12][13]. We recently demonstrated the efficiency of chitosan membranes associated with unripe banana peel extracts on the growth inhibition of Staphylococcus aureus and Escherichia coli, most common bacteria found in skin wounds [9].…”
Section: Ftir Analysismentioning
confidence: 99%
“…It is antioxidant and antimicrobial (bacterial, fungal, and yeast activities) and demonstrates higher concentration of phenolic compounds and mineral content [9][10][11]. The healing and antimicrobial properties of banana peel are associated with the presence of tannin, which are found in higher concentration in the unripe banana peel [12,13]. Thus, association of chitosan and unripe banana peel might be a great alternative of a low-cost biomaterial for wound dressing application.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of most of the banana peel varieties is correlated with the tannins present, which are believed to have protein precipitating capacity credited to the astringent action which ultimately affects bacterial peptidoglycan. 64 Several authors have supported the fact of using BP for the production of various natural dyes that can protect cotton fabrics against harmful bacterial effects. 65 The banana peel (aqueous extract) has a persuasive antibacterial effect.…”
Section: Antimicrobial Potential Of Banana Peelmentioning
confidence: 95%
“…Despite a limited number of studies regarding the antimicrobial potential of BP, particularly in vitro , several authors reported the role of phenolic compounds in inhibiting the growth and development of spoilage and pathogenic microorganisms through different mechanisms. The antibacterial activity of most of the banana peel varieties is correlated with the tannins present, which are believed to have protein precipitating capacity credited to the astringent action which ultimately affects bacterial peptidoglycan . Several authors have supported the fact of using BP for the production of various natural dyes that can protect cotton fabrics against harmful bacterial effects .…”
Section: Antimicrobial Potential Of Banana Peelmentioning
confidence: 99%
“…Apabila dinding sel rusak maka hal tersebut akan mengganggu kegiatan dalam sel sehingga sel tersebut juga akan rusak dan mati. Jadi, tanin berfungsi untuk merusak dinding sel bakteri Staphylococcus aureus (Dalimartha, 2000;Kumar et al, 2012;Min et al, 2008;Lino et al, 2011). Tanin merupakan senyawa fenol bekerja dengan cara menghambat pertumbuhan bakteri dengan melakukan denaturasi protein, sehingga permeabilitas bakteri meningkat.…”
Section: Gambar 3 Hasil Rata-rata Diameter Zona Hambat Per Hari (Mm) Dalam 3 Hari Pengamatanunclassified